Mill's Principle of Utility: A Defense of John Stuart Mill's Notorious Proof - Alican, Necip Fikri (Value Inquiry Book Series, 1994)
This book is a thoroughgoing analysis, interpretation, and defense of John Stuart Mill's proof of the principle of utility. It answers the traditional charges levelled against that proof, supports a comprehensive interpretation by painstaking study of Mill's text in Utilitarianism , and marshals arguments on behalf of utility as the first principle of morality. Universal Justice (UJ) is dedicated to the advancement of justice conceived globally. It publishes interpretations of the history of thought as well as original monographs and collective volumes, including work related to the activities of the International Society for Universalism.